Editing Documentary Together with Editors - Ngik Tiin, Loh; Doris Ding, Kiing; Evangelyne Bellarmine, Amba; Chong Lee, Yow (Mini Film Festival, 2022)
Infographics on "editing documentary together with editors". The content is extracted from MFF Doc Workshop (3) presented by Ms. Ditsi Carolino, designed by Ngik Tiin, Doris, Eva, advised and edited by Yow.